Discovery of a Highly Selective Cell‐Active Inhibitor of the Histone Lysine Demethylases KDM2/7. (7th November 2017) - Gerken, Philip A.; Wolstenhulme, Jamie R.; Tumber, Anthony; Hatch, Stephanie B.; Zhang, Yijia; Müller, Susanne; Chandler, Shane A.; Mair, Barbara; Li, Fengling; Nijman, Sebastian M. B.; Konietzny, Rebecca; Szommer, Tamas; et al.
Abstract: Histone lysine demethylases (KDMs) are of critical importance in the epigenetic regulation of gene expression, yet there are few selective, cell‐permeable inhibitors or suitable tool compounds for these enzymes. We describe the discovery of a new class of inhibitor that is highly potent towards the histone lysine demethylases KDM2A/7A. A modular synthetic approach was used to explore the chemical space and accelerate the investigation of key structure–activity relationships, leading to the development of a small molecule with around 75‐fold selectivity towards KDM2A/7A versus other KDMs, as well as cellular activity at low micromolar concentrations.